PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SKETCHFAB PADA MATERI ORGAN PENCERNAAN MANUSIA DI KELAS V SDN 060851 KEC. MEDAN PERJUANGAN - Jerina Basita Aprilia Br Situkkir; Lidia Simanihuruk; Nurhairani; Fahrur Rozi; Nurhudayah Manjani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to develop Sketchfab-based learning media and determine its validity, practicality, and effectiveness. The study used the Research and Development (R&D) method with the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 21 fifth-grade students of SDN 060851, Medan Perjuangan District. Data collection was conducted through observation, interviews, validation questionnaires, practicality questionnaires, and learning outcome tests in the form of pre-tests and post-tests. Data were analyzed using quantitative descriptive analysis and N-Gain calculations. The results of the study showed that the Sketchfab-based learning media achieved an average validity percentage of 89.5%, categorized as very feasible, a practicality test score of 92.5%, categorized as very practical, and an effectiveness test result of 0.77, categorized as high. This was evidenced by the increase in students' average score from 49.90 in the pre-test to 87.43 in the post-test. These results indicate that the Sketchfab-based learning media is able to improve students' understanding of the Human Digestive Organs and is suitable for use as a learning medium in the fifth grade science subject of elementary school.